2023
DOI: 10.1021/acsomega.3c00757
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Optoelectronic and Thermoelectric Properties of CdTe Systems in Different Phases: A First-Principles Study

Abstract: CdTe is a potential material for making efficient and stable solar cells. The present study aimed to systematically investigate the electronic, optical, and thermoelectric properties of different structural phases of CdTe using density functional theory. The electronic properties were calculated using the modified Becke−Johnson potential with the local density approximation (LDA) correlation. The band structure profiles showed a direct band at the Γ-point for α-cubic, β-hexagonal, γ-orthorhombic, and an indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Stable materials feature a smooth and well-behaved phonon dispersion plot with no negative frequencies or imaginary modes. 37,38 The CASTEP package, 39 which also operates within the context of DFT, is used for obtaining the phonon dispersion plots of the materials under investigation as displayed in Fig. 2(a)–(c).…”
Section: Resultsmentioning
confidence: 99%
“…Stable materials feature a smooth and well-behaved phonon dispersion plot with no negative frequencies or imaginary modes. 37,38 The CASTEP package, 39 which also operates within the context of DFT, is used for obtaining the phonon dispersion plots of the materials under investigation as displayed in Fig. 2(a)–(c).…”
Section: Resultsmentioning
confidence: 99%
“…The phonon dispersion plot of stable materials is smooth and well-behaved, with no negative frequencies or imaginary modes. The CASTEP software [49], which also works within the context of DFT, is used to compute the phonon dispersions plots of the materials under research, as shown in figures 4(a), (b). The phonon dispersion calculations predicted and validated the stable nature of the studied materials.…”
mentioning
confidence: 99%